When the biography and the body are transformed into a judicial test. Karina's case: violence, self-defense and a state of justifying need - Castelletti Font, Claudia (2018)
Gender analysis of the biography, space, time, and marks of violence on the body of a woman can serve as defense and legal evidenc to establish a defense to criminal liability. It examines the unique Chilean case has been acquitted of a woman accused of killing her partner by defense inextreme circunstances, and gender bias of the prosecutor.